Augustus : Image and Substance. - Levick, Barbara (Taylor and Francis, 2014)
Throughout a long and spectacularly successful political life, the Emperor Augustus (63BC-AD14) was a master of spin. Barbara Levick exposes the techniques which he used to disguise the ruthlessness of his rise to power and to enhance his successes once power was achieved. There was, she argues, less difference than might appear between the ambitious youth who overthrew Anthony and Cleopatra and the admired Emperor of later years. However seemingly benevolent his autocracy and substantial his achievements, Augustus' overriding purpose was always to keep himself and his dynasty in po.